STUDY OF INTESTINAL HELMINTHS OF SWINE FROM CHIKUN AND JEMA’A LOCAL GOVERNMENT AREAS OF KADUNA STATE, NIGERIA - Nwokoye, Chibuzor; Onusiriuka, Benjamin; Yahaya, Umar; Dikwa, Karderam Bukar (FUDMA Journal of Sciences, 2021)
A study was conducted between May and August, 2018 to determine the prevalence of intestinal helminths of pigs in Chikun and Jema’a Local Government Areas, Kaduna State. 203 faecal samples were collected, processed and examined under light microscopy. Intestinal helminths recorded were: Ascaris suum(57.1%), Oesophagostomum dentatum(37.0%), Hyostrongylus rubidus(14.8%), Metastrongylus elongates(8.9%), Strongyloides(4.5%), Stepanurus dentatum(2.5%), Trichuris suis(1.5%), Globocephalus urobuslatus(2.0%) and Physocephalus sexalatus(1.5%). The overall prevalence of helminth infection in both LGAs was 71.9%. Pigs in Jema’a LGA had significantly higher prevalence (87.9%) than pigs from Chikun LGA (56.7%). Female pigs had relatively higher (74.4%) infection than male pigs (68.6%). This pattern was also reflected in Chikun LGA where female pigs had a prevalence of 63.9% compared to 46.5% in males, however, the reverse was the case in Jema’a LGA where males had 90.7% prevalence and females 85.7%. In Chikun LGA, the highest prevalence of 58.6% was recorded among pigs aged 25-36 months, followed by pigs aged 5-12 months with prevalence of 57.1%, and the least prevalence of 55.0% was recorded in pigs aged 13-24 months. The prevalence of intestinal helminthosis in pigs tends to decrease with age in Jema’a LGA. The presence of these parasites in pigs examined indicates a potential public health problem in Chikun and Jema’a Local Government Areas of Kaduna state. Enlightenment of pig farmers on the need for periodic veterinary care and restriction of stray pigs through legislation formulation and enforcement are recommended as control measures
Keywords: Swine, Helminths, Faecal, Prevalence, Gender, Age